An Attempt at the Classification of a Quarter of (Non-Critical) Corporate Social Reporting - Woodward, David G (The International Journal of Accounting and Business Society, 1998)
Whilst  corporate  social responsibility (CSRes  hereafter)  perhaps has a long history,  corporate  social reporting  (CSRep  hereafter)  is  probably  of more  recent origin.  Thus  although  Guthrie  and  Parker  (1989)  were  able  to  show  in  their longitudinal study of Broken Hill Proprietary eyidence of CSRep activity (as revealed via the company's annual reports), going back to the last century, such studies remain a rarity (although see also Hogner 1982; and Niemark  1992).The major early developments in the field of CSRep seem to have occurred in the USA in the earlv  1970s. with the emergence of two parallel initiatives.Firstly,  there  was  the  development  of  what  might  be  called  generalised models  of CSRep.  These  were  m  some cases  highly theoretical  and exhibited great difficulty  of  application  to  real  life  organisations